Prevalence of Low Birth Weight and its Association With Anemia in White Nile State, Sudan: A Cross-Sectional Study - Abdelmageed Elmugabil; Abdullah Al-Nafeesah; Ashwaq AlEed; Nadiah AlHabardi; Ishag Adam (SAGE Publishing, 2023)
Introduction Low birth weight (LBW) remains a global health concern, especially in sub-Saharan African countries with fewer resources, such as Sudan. Despite ongoing preventive measures, LBW is still one of the main health problems and it is a leading risk factor for several adverse perinatal and neonatal outcomes. Objective To assess the prevalence of and factors associated (mainly maternal anemia) with LBW at Rabak Maternity Hospital, White Nile, Central Sudan. Methods A cross-sectional study was conducted involving live singleton newborns and their mothers who presented to Rabak Maternity Hospital from September to December 2021. Questionnaires were completed via face-to-face interviews to gather maternal information (maternal age, parity, history of miscarriage, educational status, and level of antenatal care [ANC]). Maternal hemoglobin levels were measured using an automated hematology analyzer. The neonate's birth weight and sex were recorded. Results Two hundred and fifty-three newborns were enrolled in this study, 40 (15.8%) of whom were LBW neonates. The median (interquartile range) maternal age and parity were 25 (21.0-30.0) years and 2 (1-4), respectively. While gestational age, maternal hemoglobin, and maternal anemia were associated with LBW, maternal age, parity, a history of miscarriage, education level, and level of ANC were not associated with LBW in the univariate analysis. Multivariate analysis showed that gestational age (adjusted odds ratio [AOR] = 0.80, 95% confidence interval [CI] = 0.66-0.96) and maternal hemoglobin (AOR = 0.76, 95% CI = 0.52-0.86) were inversely associated with LBW. Maternal anemia was associated with LBW (AOR = 4.70, 95% CI = 2.06-10.94). Conclusion LBW is a major health concern in White Nile, Sudan. Maternal age and maternal anemia are associated with LBW. Preventive measures for managing maternal anemia may help reduce the incidence of LBW.